Analisis Analisis Kesulitan Passing Bawah Bola Voli Pada Kelas Xi SMAN 13 Medan: Bola Voli - Purba, Ilham Ari Affandi Purba; Siregar, Samsuddin; Ritonga, M Fauzan; Putra, Rifqi Andriansyah (JPKO Jurnal Pendidikan dan Kepelatihan Olahraga, 2024)
Underpassing is a crucial basic technique in volleyball, serving as the foundation forteam success. This research aims to analyze the difficulties of class XI students atSMAN 13 Medan in making down passes. The method used was a direct surveyduring volleyball practice. The results of the analysis show that the low selfconfidence factor has a significant effect on students' abilities. Of the 30 studentsanalyzed, the difficulty categories were divided as follows: "both arms are not closed"(20 students), "both arms are not tightened" (9 students), "the ball hit the palm of thehand" (6 students), "arms too high when receiving the ball” (6 students), and “lowself-confidence” (5 students). The advice given is for teachers to pay more attentionto and evaluate student movements and build motivation in the learning process. It ishoped that this research can become a basis for understanding students' difficulties inpassing volleyball in the future.